City-regional councils: a myth or method for better planning? The case of the Khomas region (Namibia) - Detering, A. R.; Campbell, M.; De Kock, J. (University of the Free State, 2005)
English: The functions to be fulfilled by regional councils cannot be performed adequately by the Khomas Regional Council, due to the Council’s lack of funds, capacity, expertise and experience. The Windhoek Local Authority Council, in comparison, occupies a very dominant position in terms of size, financial standing and expertise. At present there is virtually no co-operation between these institutions. It will be proposed that a ‘city-regional council’ be formed, which would enable the joint administration of the Windhoek Local Authority area and the Khomas Region’s urban fringe developments, settlements and rural areas. It is anticipated that this proposed joint administration for the area will streamline planning processes and speed up decision-making.

Afrikaans: As gevolg van ’n gebrek aan fondse, kapasiteit, kundigheid en ondervinding kan die Khomas Streeksraad nie die funksies, soos vereis word van streeksrade, uitvoer nie. In vergelyking hiermee is die Windhoek Plaaslike Owerheidsraad wat betref grootte, finansies en kundigheid in ’n baie beter posisie. Tans bestaan daar byna geen samewerking tussen genoemde twee liggame nie. Daar sal voorgestel word dat ’n ‘stad-streeksraad’ tot stand moet kom wat die gesamentlike administrasie van die Windhoek Plaaslike Owerheidsraad se gebied en die Khomas Streeksraad se stedelike randgebiede, nedersettings en landelike gebiede moontlik sal maak. Die verwagting is dat hierdie voorgestelde gesamentlike administrasie van die gebied beplanningprosesse sal vereenvoudig en besluitneming sal bespoedig.
Keywords: Windhoek Local Authority Council; Khomas Region; Namibia